2014
DOI: 10.1787/eco_studies-2013-5k3tq96mbr44
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the pace of fiscal consolidation

Abstract: In many OECD countries debt has soared to levels threatening fiscal sustainability, necessitating its reduction over the medium to longer term. This paper proposes a stylised model, featuring endogenous interactions between fiscal policy, growth and financial markets, to highlight how economic shocks and structural features of an economy can affect consolidation strategy and resulting growth and inflation developments. The fiscal authorities are assumed to choose a consolidation path from a predetermined set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…This is why it is needed to predict and implement consolidation adjustments in advance. Rawdanowicz (2014) found that in the case of immediate start of consolidation, the debt-to-GDP ratio change would only be reflected after seven or eight years.…”
Section: Determinants Of Fiscal Consolidation Startmentioning
confidence: 98%
“…This is why it is needed to predict and implement consolidation adjustments in advance. Rawdanowicz (2014) found that in the case of immediate start of consolidation, the debt-to-GDP ratio change would only be reflected after seven or eight years.…”
Section: Determinants Of Fiscal Consolidation Startmentioning
confidence: 98%
“…Rawdanowicz (2012) shows that it is possible to choose an optimal consolidation path to bring the deficit down and stabilise debt at a long-run target in a finite horizon. A previous OECD project on fiscal consolidation , Barrell et al (2012) and Merola and Sutherland (2012) stressed the need to structure a consolidation strategy such that instruments with low multipliers are used initially and to enhance the institutional framework for fiscal policy in order to minimise the trade-offs with growth in the short run.…”
Section: Fiscal Rules For Countries In Transition Towards a Lower Prumentioning
confidence: 99%
“…See Rawdanowicz (2012) and Carnot (2014) who provide a rule for determining the structural budget balance effort with the two objectives of debt sustainability (with debt target) and macroeconomic stabilisation and illustrate the calibration.…”
mentioning
confidence: 99%
“…With policy interest rates at their effective lower bound, further stimulus would have to come from unconventional measures, including QE, forward guidance or schemes to provide funding to banks. There is some evidence that the effectiveness of such measures may decline as they are used more extensively and asset prices become richly valued (Rawdanowicz et al, 2013). Thus, their effectiveness in addressing the problem of hysteresis is not certain as they may also encourage excessive risk-taking and asset price booms that lead to financial instability and costly recessions.…”
Section: Short-term Policy Implicationsmentioning
confidence: 99%
“…The pace of structural fiscal adjustment could be slowed in some countries if this is in line with EU fiscal rules and does not undermine market confidence. Too ambitious consolidation in the presence of hysteresis effects, high fiscal multipliers and interest rate shocks can result in a protracted spell of negative output gaps and deflation which reduces the level of potential output (Rawdanowicz, 2013). The limited room for fiscal stimulus stresses the importance to raise public sector efficiency and implement growth-friendly budget neutral changes in the structure of government revenue and spending (Cournède et al, 2013).…”
mentioning
confidence: 99%